2014
DOI: 10.1007/s10489-014-0517-1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic distributed lanes: motion planning for multiple autonomous vehicles

Abstract: Unorganized traffic is a generalized form of travel wherein vehicles do not adhere to any predefined lanes and can travel in-between lanes. Such travel is visible in a number of countries e.g. India, wherein it enables a higher traffic bandwidth, more overtaking and more efficient travel. These advantages are visible when the vehicles vary considerably in size and speed, in the absence of which the predefined lanes are near-optimal. Motion planning for multiple autonomous vehicles in unorganized traffic deals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Centralized MAP involves using an intermediary agent that has complete knowledge of the task. The distributed or decentralized approach spreads the planning responsability among agents, which are in charge of interacting with each other to coordinate their local solutions, if necessary [28,18]. The adoption of a centralized approach is aimed at improving the planner performance by taking advantage of the inherent structure of the MAP tasks [22,8].…”
Section: Related Workmentioning
confidence: 99%
“…Centralized MAP involves using an intermediary agent that has complete knowledge of the task. The distributed or decentralized approach spreads the planning responsability among agents, which are in charge of interacting with each other to coordinate their local solutions, if necessary [28,18]. The adoption of a centralized approach is aimed at improving the planner performance by taking advantage of the inherent structure of the MAP tasks [22,8].…”
Section: Related Workmentioning
confidence: 99%
“…The average speed includes any time spent in waiting for traffic lights at V 2 (if any). In a related publication [20], we showed that vehicles may be waiting for prolonged times at the traffic crossings and hence, accounting for this waiting time is important.…”
Section: Algorithmmentioning
confidence: 99%
“…The factor is only of importance when there are far too many vehicles waiting to cross an intersection, and as in other cases, the queue clears well before this factor comes into play. Complete details regarding the traffic light operations can be found in Kala [22].…”
Section: Traffic Simulationmentioning
confidence: 99%
“…A synthetic overtaking scenario is shown in Figure 2. Complete details regarding the overtaking procedure can be found in Kala [22].…”
Section: Single-lane Overtakingmentioning
confidence: 99%